The experiences of parents and caregivers of children with disability on community-based rehabilitation (CBR) services in Malaysia: A Qualitative study - Hasan, Haliza; Syed Junid, Syed Mohamed Al Junid (2019)
Background: The rehabilitation program for disabled children is provided through community-based rehabilitation (CBR) services by an initiative of the Department of Social Welfare Malaysia. This long-term program needs commitment and compliance, which relates to the quality of services experienced by parents and caregivers. Thus, the purpose of this study was to explore the experiences of the parents and caregivers of disabled children on the CBR services. Methods: This qualitative study utilized in-depth interview sessions held from March to May 2015. Fifteen parents and caregivers who had disabled children participating in the CBR program were selected using a purposive sampling method. All recorded conversations were transcribed verbatim and analyzed using Atlas.ti version 8.0. The thematic analysis was used for identifying, analyzing, and reporting the data obtained. The themes that emerged were read, reread, and peer checked until the researcher agreed on the thematic representation of the data. Results: Six major themes emerged from this study, including CBR activity, facilities, environment, communication, program impact, and management system. Conclusion: The majority of the parents and caregivers had good experiences with CBR services. However, several aspects could be given further attention to improve the CBR quality and to sustain its services for disabled children.